2016
DOI: 10.1073/pnas.1611118114
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric unwrapping of nucleosomal DNA propagates asymmetric opening and dissociation of the histone core

Abstract: The nucleosome core particle (NCP) is the basic structural unit for genome packaging in eukaryotic cells and consists of DNA wound around a core of eight histone proteins. DNA access is modulated through dynamic processes of NCP disassembly. Partly disassembled structures, such as the hexasome (containing six histones) and the tetrasome (four histones), are important for transcription regulation in vivo. However, the pathways for their formation have been difficult to characterize. We combine time-resolved (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
114
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(137 citation statements)
references
References 37 publications
20
114
0
3
Order By: Relevance
“…The asymmetric DNA unwrapping on the nucleosome core observed in the Figure S13 and Supplementary Table S4 for more details of the fitting procedure. solution SAXS experiment is dependent on local DNA sequence (75,76) and has been observed previously (73,76,77). We also observed lower salt-dependent stability and lower affinity for Telo-NCP compared to the other DNA sequences investigated.…”
Section: The Telo-ncp Exhibits a Stable Yet Dynamic Structure In Solusupporting
confidence: 86%
“…The asymmetric DNA unwrapping on the nucleosome core observed in the Figure S13 and Supplementary Table S4 for more details of the fitting procedure. solution SAXS experiment is dependent on local DNA sequence (75,76) and has been observed previously (73,76,77). We also observed lower salt-dependent stability and lower affinity for Telo-NCP compared to the other DNA sequences investigated.…”
Section: The Telo-ncp Exhibits a Stable Yet Dynamic Structure In Solusupporting
confidence: 86%
“…In both systems we note that nucleosome stability is enhanced by strong DNA-dimer interactions, which are roughly equal in strength in H2A and H2A.B containing systems. This is in line with experiments which have shown that DNA is required for nucleosome stability at physiological salt concentrations, and that the histone core will only assemble at high salt concentrations without DNA (61)(62)(63). We note that the MM/GBSA analysis presented here is relatively crude and does not include important thermodynamic terms such as conformational entropy and explicit solvation, therefore although the trends are of qualitative value, care should be taken in quantitative interpretation of the energetic values (64-68).…”
Section: Simulations Of Compact States Show Weaker Interfaces In H2asupporting
confidence: 90%
“…This phenomenon and the observed asymmetric unwrapping in the dinucleosome, occur in a way that reduces the energy cost of the bent DNA. In experiments, different features of the unwinding such as the asymmetric and symmetric openings have been observed with different probabilities [22,[30][31][32]. The different patterns of the unwinding of the dinucleosome can be understood from the energy landscape, (see Fig.…”
Section: Discussionmentioning
confidence: 99%